Influence of Technology in Realizing Smart Cities: Systematic Literature Review - Nigrum, Widian; Oktavia, Elfitri; Syah, Nurhasan; Catri, Indra (Postgraduate School, Universitas Negeri Padang, 2024)
This study examines the role of digital technology in realizing smart cities, aiming to identify its transformative potential in urban development. A systematic review methodology was applied, analyzing literature from 2019 to 2023 obtained from databases such as PubMed, Scopus, and Google Scholar, using PRISMA guidelines. The inclusion criteria focused on studies about the influence of technology in smart city development, with articles written in English or Indonesian, and restricted to original research.The review identified 3,000 articles, narrowed to five after screening for relevance and eligibility. The results highlight that digital transformation is fundamental to the smart city concept, facilitating efficiency, better resource management, and enhanced public services. For instance, implementing e-government in Sumenep Regency demonstrated how digital innovation fosters integrated governance, while Klaten Smart City showcased improvements in decision-making and operational efficiency. Digital technology enables interconnected systems, fostering collaborations among governments, private sectors, and communities.In conclusion, technology significantly reshapes urban landscapes, offering solutions for modern urban challenges such as resource allocation and citizen engagement. Smart city initiatives exemplify how digital transformation enhances urban living and sustainability, laying a foundation for future advancements.